Efficient and Secure Node Recovery in Wireless Sensor and Actor Network Using Minimal Topology Changes (International Journal of Engineering and Computer Science, 2014)
In wireless sensor-actor networks, sensors probe their surroundings and send their data to actor nodes. Actors collaboratively react to achieve predefined application mi. Since actors have to synchronize their operation, it is necessary to hold a highly connected network topology all the time. Moreover, the length of the inter-actor connection paths may be constrained to meet latency requirements. Failure of an actor may cause the network to separate into disjoint blocks and break such connectivity. One of the effective restoration methodologies is to autonomously reposition a subset of the actor nodes to restore connectivity. Contemporary restoration schemes either impose high node relocation over-head or extend some of the inter-actor data paths. This paper overcomes these drawbacks and presents a Least-Disruptive topology Repair (LeDiR) algorithm. LeDiR relies upon the local view of a node about the network to devise a recovery plan that relocates   minimum number of nodes and ensures that no path between any pair of nodes is expanded. The performance of LeDiR is examined mathematically and validated through extensive simulation experiments.